Recalcitrant Basal Cell Carcinoma after Grenz Ray Therapy: Introduction of High-Intensity Focused Ultrasound for Minimally Invasive Management - Jørgen Serup; Tomasz Zawada; Torsten Bove (Karger Publishers, 2024)
Introduction: Grenz ray therapy popular in dermatology decades ago causes multiple and recalcitrant skin cancer in the treated field many years later. The treatment of choice is surgical excision, but limitations especially disfiguring scarring are a major challenge. We introduce 20 MHz high-intensity focused ultrasound (HIFU) as a new therapy overcoming the limitations of excisional surgery. Case Presentation: A 66-year-old female, who in the 1980s had received several grenz ray treatments of the scalp, developed multiple basal cell carcinomas in the field. She had over 30 excisional surgeries including Mohs surgery in the past with many local complications but, nevertheless, recurrent cancers. HIFU treatments applied to eight basal cell carcinomas and two precancerous lesions resulted in complete clearing at 12-month control, but one recurrence after 15 months. Conclusion: The HIFU treatment is convenient, with very few complications, and applicable to field eradication of skin premalignancies and malignancies. HIFU may fill out a hitherto unmet need of both preventive and curative treatment with better long-term control of patients with recalcitrant skin cancer after grenz ray given in the past. HIFU is a new potentially important therapeutic modality in skin oncology, combining curative treatment, field eradication, and prevention in one procedure through treatment of lesions in different states of progression.